Interlanguage system to represent present and past event by students of smp muhammadiyah 6 surakarta academic year 2013/2014 - Utariningsih, Wheny; , Prof. Dr. Endang Fauziati, M. Hum; , Muamaroh, Ph.D (2014)
This study aims at identifying and describing the interlanguage system by the eighth grade students of SMP Muhammadiyah 6 Surakarta in their composition based on verb, copula be and auxiliary. The type of this research is descriptive qualitative research. In gathering written materials, the researcher uses document analysis technique which involves several steps as the research gives instruction to write recount text, the researcher reads each student's text objectively and cautiously, the researcher writes all the erroneous sentences found in student's text, the researcher lists them and makes them as the data of her research. The result of this research shows that the eighth grade students of SMP Muhammadiyah 6 Surakarta made many type of language (or linguistic system) in the process of learning a target language. The writer found 260 type language systems from student's composition, there are two classifications of interlanguage system based on interlanguage system which represents present event and interlanguage system which represents past event. The representative of interlanguage system in using of verb is the use of Be + Verb ing instead of V1, the use of Be + V1 instead of Verb1, the use of Verb-ing instead of Verb 1and the use of Verb 2 instead of V1. The representative of interlanguage system in using of copula be is the omission of Be as predicate. The representative of interlanguage system in using of auxiliary is the use of auxiliary + Verb-ing instead of auxiliary+ Verb O, the use of auxiliary Could + Verb O Instead of auxiliary Can +VO. The representative of interlanguage system in using of verb is the use of Verb 1 instead of Verb 2, the use of Verb-ing instead of Verb 2. The representative of interlanguage system in using of copula be is the use of Be present instead of Be past tense, the use of Be Was instead of Were, the use of Be Were instead of Was. The representative of interlanguage system in using of auxiliary is the use of auxiliary+ Verb-ing Instead of auxiliary+ Verb 1, the use of auxiliary Can + Verb O instead of auxiliary Could + Verb O.